2018
DOI: 10.1155/2018/7238464
|View full text |Cite
|
Sign up to set email alerts
|

Normative Values of Peripapillary Retinal Nerve Fiber Layer Thickness in a Middle Eastern Population

Abstract: Purpose Peripapillary retinal nerve fiber layer (pRNFL) thickness is subject to high variability. Normative values of pRNFL thickness remain undocumented in the Middle East. The aim of our study is to assess the normative values of pRNFL thickness in a Middle Eastern population. Methods A retrospective chart review of 74 patients was conducted. Outpatients who had presented to the ophthalmology clinic at the Jordan University Hospital between January 2016 and July 2018 were consecutively sampled. Measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
5
2
0
Order By: Relevance
“…This value is consistent with that of the previous studies on the Caucasian population using the Spectrally OCT 270+/− 22.5 um [4,10]. Based on previous studies we have noticed that middle Eastern population sample investigated in our study had thinner central foveal thickness when compared to the Iranian population but thicker than other populations like African Americans, Japanese White American, Indians and blacks (5,11,(16)(17)(18)(19)(20). Moreover, the results are variable when compared to other Caucasians [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This value is consistent with that of the previous studies on the Caucasian population using the Spectrally OCT 270+/− 22.5 um [4,10]. Based on previous studies we have noticed that middle Eastern population sample investigated in our study had thinner central foveal thickness when compared to the Iranian population but thicker than other populations like African Americans, Japanese White American, Indians and blacks (5,11,(16)(17)(18)(19)(20). Moreover, the results are variable when compared to other Caucasians [8].…”
Section: Discussionsupporting
confidence: 92%
“…The central area of the fovea increased with age while the thickness in the other areas decreased. Other areas of the retina were evaluated in the Middle Eastern population namely, the peri-papillary nerve fiber layer, this analysis concluded that the thickness in various areas is consistent with previous studies [19], Essentially, the African-American race was a predictor of decreased mean foveal thickness when compared to Caucasians and Hispanics.…”
Section: Discussionsupporting
confidence: 83%
“…The central area of the fovea increased with age while the thickness in the other areas decreased. Another areas of the retina was evaluated in the Middle Eastern population namely, the peri-papillary nerve fiber layer, this analysis concluded that the thickness in various areas is consistent with previous studies [20 ], Essentially, the African-American race was a predictor of decreased mean foveal thickness when compared to Caucasians and Hispanics. Furthermore, males were associated with increased mean foveal thickness.…”
Section: Discussionsupporting
confidence: 82%
“…Japanese have thicker retinas compared to the US population using Stratus OCT [18]. concluded that the thickness in various areas is consistent with previous studies [20], Essentially, the African-American race was a predictor of decreased mean foveal thickness when compared to…”
Section: Dsupporting
confidence: 86%
“…Refractive error didn't statistically add to the prediction model. Americans, Japanese White American, Indians and blacks (5,11,(16)(17)(18)(19)(20). Moreover, the results are variable when compared to other Caucasians [9].…”
Section: Dmentioning
confidence: 99%